1999
DOI: 10.1108/14634449910298169
|View full text |Cite
|
Sign up to set email alerts
|

Empowerment in small businesses

Abstract: The concept of empowerment has received a great deal of attention in recent years. However, the empowerment knowledge base is predominantly large company‐oriented with little evidence of understanding what empowerment means in a small business context. It is inappropriate to treat the small firm as a microcosm of a large organisation. The small business is qualitatively as well as quantitatively different and this article propounds that it is questionable whether the concept of empowerment and its various dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Although finding individuals with values similar to the organisation may assist in embedding CSR, it does not get past the base problems of reduced selection pools and a lack of resources to pay competitive compensation, use professional recruitment and invest in training found both in fair trade and in other SMEs (Rainnie 1989, Wyer & Mason 1999, De Kok & Uhlaner 2001, Cassell et al 2002, Szamosi et al 2004). Our data have some valuable insights to assist SMEs in dealing with reduced selection pools.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although finding individuals with values similar to the organisation may assist in embedding CSR, it does not get past the base problems of reduced selection pools and a lack of resources to pay competitive compensation, use professional recruitment and invest in training found both in fair trade and in other SMEs (Rainnie 1989, Wyer & Mason 1999, De Kok & Uhlaner 2001, Cassell et al 2002, Szamosi et al 2004). Our data have some valuable insights to assist SMEs in dealing with reduced selection pools.…”
Section: Discussionmentioning
confidence: 99%
“…HR and CSR in micro and small organisations [<10, and between 10 and 50 employees, respectively (European Commission 2003)] are far more interwoven than in large organisations, with the same groups or individuals being the decision makers for most business decisions (Quinn 1997, Mazzarol 2003, Spence et al 2003, Murillo & Lozano 2006). Although this should mean closer parity between selection and socialisation on the one hand, and organisational strategy for CSR on the other, there are many problems for HR in SMEs such as reduced selection pools and a lack of resources to pay competitive compensation, use professional recruitment or invest in training (Rainnie 1989, Wyer & Mason 1999, De Kok & Uhlaner 2001, Cassell et al 2002, Szamosi et al 2004) – all of which impede the ability of the organisation to implement its strategy. They are almost certain to be less formalised in their HR practices (Hill & Stewart 2000) and similarly less likely to rely on policy, codes and procedure in their CSR practice (Graafland et al 2003).…”
Section: Hr and Csrmentioning
confidence: 99%
“…Although past studies have shown that role ambiguity can affect the job performance of employees in the service setting, most of them were conducted abroad, thus very little evidence exists to understand the job performance of employees in the context of Malaysia. Furthermore, most SME researches in Malaysia focused on productivity and skill shortages (Yogeesvaran, 2005;Hamzah & Ho, 1994;Tan, 1996;Saleh & Ndubisi, 2006), entrepreneurial problems (Abdullah, Hamali, Deen, Saban & Abdurahman, 2009), TQM and organizational performances (Sohail & Hoong, 2003), empowerment (Wyer & Mason, 1999), ICT adoption among SMEs (Alam & Ahsan, 2007), SMEs historical development (Hashim, 2000), staff training and SMEs performance (Jamaludin & Hasun, 2007) and assessment criteria of banks towards small business borrowers (Mahmood & Rahman, 2007). Given such a situation, it necessitates this study to be carried out in view of the importance of the service sector SMEs in Malaysia.…”
Section: Smes In Malaysiamentioning
confidence: 99%
“…Though empowerment practice is observed to be predominantly large company oriented, Wyer and Mason (1999) state its significance in small business as well. Using insights from a case study of a Malaysian furniture manufacturer, the authors suggest in their findings that empowering management approaches are key features of successful growth-oriented small firms and facilitates sustainable development (Wyer & Mason, 1999).…”
Section: Understanding Empowermentmentioning
confidence: 96%
“…Using insights from a case study of a Malaysian furniture manufacturer, the authors suggest in their findings that empowering management approaches are key features of successful growth-oriented small firms and facilitates sustainable development (Wyer & Mason, 1999). Empowerment seems to be gaining popularity as more and more organizations embrace the concept.…”
Section: Understanding Empowermentmentioning
confidence: 98%